The problematic relationship between energy security and US national security strategies in light of the international system - Mahmmud, Asst.Prof.D. Rebwar Karim Mahmmud; Zorab, Asst.L. Sivan Salh (Sulaimani Journal for Humanities, 2025)
The relationship between energy security and American national security strategies is one of the security challenges associated with American policy at the internal and external levels, especially in light of the international system at the present time. The research clarifies the form of the relationship between them. In addition to determining whether the energy security variable may ultimately serve the American national security strategy. American energy security is governed by a set of factors, considerations and dimensions, some of which are the material and internal capabilities of the state, and its ability to efficiently use and optimally employ those resources with the aim of achieving self-sufficiency, as well as the use of soft and flexible diplomatic tools, or hard power to compensate for the shortfall in its energy resources necessary to achieve energy security on the one hand, and economic development and well-being on the other hand. All of which are tools for building the solid foundations of the American national security strategy. Hence, the research addresses the main aspects of the relationship between energy security and American national security strategies, by examining matters related to the importance of energy security in the internal and foreign policies of the United States of America.
Keywords: Energy security; National security strategy; Strategic autonomy; Petroleum politics